2020
DOI: 10.1097/qco.0000000000000671
|View full text |Cite
|
Sign up to set email alerts
|

Sapovirus: an emerging cause of childhood diarrhea

Abstract: Purpose of review: Sapovirus, a genus in the Caliciviridae family alongside norovirus, is increasingly recognized as an important cause of childhood diarrhea. Some challenges exist in our ability to better understand sapovirus infections, including the inability to grow sapovirus in cell culture, which has hindered diagnosis and studies of immunity. Another challenge is that individuals with sapovirus infection are commonly co-infected with other enteric pathogens, complicating our ability to attribute the dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 112 publications
2
56
0
Order By: Relevance
“…Many other studies have reported mixed infections of sapovirus with other enteric pathogens [ 27 , 39 , 40 ]. Interestingly, the detection of sapovirus in healthy controls has also been reported [ 1 , 41 ]. However, the multinational Malnutrition and Enteric Disease (MAL-ED) cohort study estimated that sapovirus has the third highest attributable incidence for diarrhea among children under 1 year of age and the second-highest attributable incidence between 1 and 2 years of age, just behind Shigella sp.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Many other studies have reported mixed infections of sapovirus with other enteric pathogens [ 27 , 39 , 40 ]. Interestingly, the detection of sapovirus in healthy controls has also been reported [ 1 , 41 ]. However, the multinational Malnutrition and Enteric Disease (MAL-ED) cohort study estimated that sapovirus has the third highest attributable incidence for diarrhea among children under 1 year of age and the second-highest attributable incidence between 1 and 2 years of age, just behind Shigella sp.…”
Section: Discussionmentioning
confidence: 94%
“…In the present study it was found that noroviruses and sapoviruses were the most prevalent enteric viruses in the study population, with positive rates of 12.22% and 8.09%, respectively, followed by rotaviruses (7.11%), human astroviruses (4.91%) and enteric adenoviruses (2.9%). The detection frequency of sapovirus has been reported to range from 1 to 17% of diarrhea cases [ 1 ], although it varies across age groups and geographical locations. Similar results have been obtained in other studies performed in the post-rotavirus vaccine era, in which norovirus, sapovirus, and rotavirus infection were identified in this order of frequency [ 20 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations